Short-Term Effectiveness and Reduction in Insulin Requirements in Patients With Type 2 Diabetes Treated With IdegLira in a Real-World Setting - Ramírez-Rincón, Alex; Builes-Montaño, Carlos E.; Hincapié-García, Jaime A.; Blanco, Victor M.; Botero-Arango, José F. (Frontiers in Endocrinology, 2022)
Background: Type 2 diabetes mellitus (T2DM) is a chronic, highly prevalent disease with a significant impact on health. Appropriate treatment requires effective and timely escalation to achieve metabolic control. To evaluate the effectiveness and safety of IDegLira on adults with T2DM previously treated with oral antidiabetics and/or insulin in a real-life setting. Methods: An observational, study in a real-world setting was conducted. Patients were selected from the outpatient clinic of two centers dedicated to specialized diabetes care. Main outcomes were HbA1c, body weight, insulin dose changes, hypoglycemia, and other adverse events. Results: 67 T2DM patients treated with IDegLira were monitored between 3 and 7 months. At the end of follow-up, the median change in HbA1c was -1.05% (CI95% -1.45, -0.65), and a decrease in insulin requirement was also observed (mean difference -10 TDD units (CI95% - 17 to -2.5). No treatment discontinuation was reported, hypoglycemia events were reported in 3 patients at the end of follow-up versus 8 patients at baseline. Conclusions: This real-life study shows the effectiveness in glycemic control of IDegLira use in T2DM patients who do not achieve goals with other therapies, with an adequate safety profile. The findings need to be confirmed with evaluation of therapeutic results in larger cohorts.